2005
DOI: 10.1016/j.jinorgbio.2005.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Decavanadate effects in biological systems

Abstract: Vanadium biological studies often disregarded the formation of decameric vanadate species known to interact, in vitro, with high-affinity with many proteins such as myosin and sarcoplasmic reticulum calcium pump and also to inhibit these biochemical systems involved in energy transduction. Moreover, very few in vivo animal studies involving vanadium consider the contribution of decavanadate to vanadium biological effects. Recently, it has been shown that an acute exposure to decavanadate but not to other vanad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 68 publications
3
100
0
Order By: Relevance
“…Recent work from our laboratory [20][21][22][23] demonstrated that an acute exposure to decameric vanadate species, but not exposure to monomeric vanadate, induces changes on vanadium accumulation and in overall stress markers. Altogether, these observations reveal that decameric vanadate plays an important role in the evaluation of vanadium (V) toxicity in biological systems [17].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Recent work from our laboratory [20][21][22][23] demonstrated that an acute exposure to decameric vanadate species, but not exposure to monomeric vanadate, induces changes on vanadium accumulation and in overall stress markers. Altogether, these observations reveal that decameric vanadate plays an important role in the evaluation of vanadium (V) toxicity in biological systems [17].…”
Section: Introductionmentioning
confidence: 82%
“…By inhibiting G-actin polymerization, decameric vanadate eventually prevents microfilaments formation and F-actin stimulation of myosin ATPase activity. However, before attempting to understand the effects promoted by each individual vanadate species that may occur in the reaction medium, it is of primary importance to characterize precisely the vanadate solutions and the interactions with the system by using 51 V NMR spectroscopy [17].…”
Section: Decavanadate Inhibition Of G-actin Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Furthermore, decavanadate, 50 and compounds containing decavanadate 51 have been reported to lower glycemic levels, 50,51 and to normalize plasma lipid profiles. 51 Due to the ability of V 10 to interfere with several biological processes, such as calcium homeostasis, muscle contraction and oxidative stress, 8,54,55 not only in vitro but also in vivo, 52,53 decavanadate has recently been associated with the treatment of Leishmaniosis. 56 In this and probably in many other cases the mechanism of action of decavanadate progresses via the inhibition of the E1-E2 Ca 2+ -ATPases.…”
Section: Ca 2+ -Atpase Inhibitorsmentioning
confidence: 99%